Metode Pembelajaran Bahasa Arab (Studi Kasus di Pondok Modern Zam-Zam Muhammadiyah Cilongok Banyumas) - Kusnan Kusnan (Institut Agama Islam Negeri Purwokerto, 2017)
Arabic is the language of Muslim’s holy book, and reading it is obligatory for Muslims. In Islamic education, Arabic is the language that should be mastered as a means of understanding the original texts of the source of Islamic law. One of the important thing in learning Arabic is the method. Zam-Zam Muhammadiyyah Modern Islamic Boarding School implements a diffent model and method of learning Arabic compared to other Islamic boarding schools in the district of Cilongok. This is a qualitative research, through a case study using interview, observation and documentation techniques for collecting data and interactive analysis for analying data. The findings of this research are three models of Arabic learning in Pondok Pesantren. The first model is khiwar or muhadatsah, the second is mufrodat walls intended to make students familiar with Arabic vocabulary, and the third is Lughoh. The method and model of Arabic learning in the institution as described above is a combined method. There are at least three methods used, i.e. Communicative Problem-Based Learning Method, Audiolingual Method, and Grammar-Translation Method.